2019
DOI: 10.1029/2018wr024004
|View full text |Cite
|
Sign up to set email alerts
|

Sediments in Agricultural Reservoirs Act as Sinks and Sources for Nutrients over Various Timescales

Abstract: Reservoirs along rivers have the potential to act as nutrient sinks (e.g., denitrification and sedimentation) or sources (e.g., decomposition and redox changes), potentially reducing or enhancing nutrient loads downstream. This study investigated the spatial and temporal variability of water and lakebed sediment chemistry for an agricultural reservoir, Carlyle Lake (Illinois, U.S.), to assess the role of sediments as nutrient sinks or sources. Samples were collected across the reservoir over a 2‐year period. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…We also hypothesized that sediment NO 3 − uptake would be higher in deeper water, and SRP uptake would be higher in shallower water. This hypothesis was based on predictions from previous studies that O 2 availability would be lower in deeper water sediments where light and primary production is excluded, as low redox potential can increase NO 3 − loss through denitrification and increase SRP release from bound sediments [18,29,51]. We found no differences in sediment nutrient flux based on water depth, and similar flux rates were observed from shore to mid-lake.…”
Section: Sediment Flux Trendssupporting
confidence: 80%
See 1 more Smart Citation
“…We also hypothesized that sediment NO 3 − uptake would be higher in deeper water, and SRP uptake would be higher in shallower water. This hypothesis was based on predictions from previous studies that O 2 availability would be lower in deeper water sediments where light and primary production is excluded, as low redox potential can increase NO 3 − loss through denitrification and increase SRP release from bound sediments [18,29,51]. We found no differences in sediment nutrient flux based on water depth, and similar flux rates were observed from shore to mid-lake.…”
Section: Sediment Flux Trendssupporting
confidence: 80%
“…The time of year and seasonality can have varying effects on nutrient fluxes. For example, Jin et al [31] observed seasonal changes in sediment P cycling, but Shaughnessey et al [18] did not observe seasonal influences on sediment N fluxes. The relationship between nutrient removal and temperature has long been established due to increased biologic activity at warmer temperatures, which, in turn, increases total nutrient retention, specifically through denitrification [65,66].…”
Section: Season As a Controlling Variablementioning
confidence: 99%
“…Custodio et al (2020) suggested that the bacterial communities in lake environments experienced stress from fish farming in the Peruvian Andes. Microorganisms usually sink into the sediment of aquaculture water and eventually become a source of nutrients for aquatic organisms (Shaughnessy et al 2019). Carbone and Faggio (2016) suggested that the microbiota played a vital role in defining the yield and quality of products from fisheries and other aquaculture environments.…”
Section: Introductionmentioning
confidence: 99%
“…Sediment pollution of water bodies can result in aquatic habitat degradation, hindered water supply, and transport of pollutants; thus, it is of major concern to watershed managers. Effective sediment management necessitates insight into active sediment sources and pathways along with their response to hydroclimatic variables, geomorphological features, and land management operations.…”
Section: Introductionmentioning
confidence: 99%